4D simultaneous tissue and blood flow Doppler imaging: revisiting cardiac Doppler index with single heart beat 4D ultrafast echocardiography. (10th April 2019) - Papadacci, C; Finel, V; Villemain, O; Goudot, G; Provost, J; Messas, E; Tanter, M; Pernot, M
Abstract: The goal of this study was to demonstrate the feasibility of semi-automatic evaluation of cardiac Doppler indices in a single heartbeat in human hearts by performing 4D ultrafast echocardiography with a dedicated sequence of 4D simultaneous tissue and blood flow Doppler imaging. 4D echocardiography has the potential to improve the quantification of major cardiac indices by providing more reproducible and less user dependent measurements such as the quantification of left ventricle (LV) volume. The evaluation of Doppler indices, however, did not benefit yet from 4D echocardiography because of limited volume rates achieved in conventional volumetric color Doppler imaging but also because spectral Doppler estimation is still restricted to a single location. High volume rate (5200 volume s −1 ) transthoracic simultaneous tissue and blood flow Doppler acquisitions of three human LV were performed using a 4D ultrafast echocardiography scanner prototype during a single heartbeat. 4D color flow, 4D tissue Doppler cineloops and spectral Doppler at each voxel were computed. LV outflow tract, mitral inflow and basal inferoseptal locations were automatically detected. Doppler indices were derived at these locations and were compared against clinical 2D echocardiography. Blood flow Doppler indices E (early filling), A (atrial filling), E / A ratio, S (systolic ejection) and cardiac output were assessed on the three volunteers. Simultaneous tissue Doppler indices e ′ (mitral annular velocity peak), a ′ (late velocity peak), e ′/ a ′ ratio, s ′ (systolic annular velocity peak), E / e ′ ratio were also estimated. Standard deviations on three independent acquisitions were averaged over the indices and was found to be inferior to 4% and 8.5% for Doppler flow and tissue Doppler indices, respectively. Comparison against clinical 2D echocardiography gave a p   value larger than 0.05 in average indicating no significant differences. 4D ultrafast echocardiography can quantify the major cardiac Doppler indices in a single heart beat acquisition.